Análise de pórticos de aço com ligações viga-pilar e de base de pilar semirrígidas a partir do método dos componentes - Leandro Albuquerque Ribeiro de Oliveira (2015)
The behavior of structural connections can be described mainly by the moment-rotation characteristic, that considering the relation between the applied bending moment in the connection and relative rotation between the connected elements, which can be defined from the fundamental properties: the initial rotational stiffness, the moment resistanceand the rotation capacity. Traditionally, the stiffness is not considered in the dimensioning of the connections, and they are designed assuming two idealized behavior: fully rigid connections (K = ), and ideally pinned connections (K = 0). However, due to the practical impossibility of designing ideal connections, the actual behavior of a connection is semi-rigid (0 <K < ). Thus, this work has as objective the study of semi-rigid behavior of beam-column connections and column basis connections from theoretical formulations via Component Method and its applications in numerical simulations of steel frames. For this, in this work, the fundamental concepts about the behavior, the classification and the different types of modeling the behavior of connections are presented in order to provide a proper understanding of the properties that determine the structural response. So some of the concepts, steps and practical procedures of implementation of the Component Method method are presented and discussed, and then presents a study of the tensioned region of connection from the Tstub model and their failure mechanisms. Furthermore, based on the European Standard,some practical procedures for design and verification of connections and for characterization and evaluation of fundamental properties (initial rotational stiffness, moment resistance and rotation capacity) are presented. Finally, numerical examples of frames with semi-rigid beam-column connections and column basis are presented, in order to evaluate the influence of the behavior of these joints in the nodal displacements, the distribution of and magnitude of the internalforces in the elements and the global stability of the structure and evaluate the validity of simplified global analysis procedures.